Digital Transformation in Human Resource Management: A Qualitative Study on Implementation, Challenges, and Impact on Employee Performance at BPS Surabaya - SIHOMBING, MARYTO MARETIS; Wibisono, Muhammad Gunawan; Sri Rahayu (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
The rapid advancement of digital technology has significantly influenced public sector institutions, including human resource management (HRM) processes. BPS Surabaya, as a government statistical agency, has adopted various digital platforms to improve efficiency, transparency, and data accuracy in employee management. This research aims to explore the forms of digital transformation implementation in HRM, identify its supporting and inhibiting factors, and analyze its impact on employee performance. A qualitative phenomenological approach was employed to gain a deep understanding of employee experiences. Data were collected through in-depth interviews with 28 respondents from different roles within BPS Surabaya. The data were analyzed using NVivo software to generate thematic coding and network visualizations that highlight key patterns and relationships. Findings show that digital tools such as SIMPEG, FASIH, KipApps, SRIKANDI, and digital attendance systems play a central role in reshaping HR practices. These applications contribute to increased efficiency, real-time monitoring, and data-driven decision-making. Supporting factors include infrastructure readiness, leadership commitment, responsive IT support, and adaptive employee attitudes. Inhibiting factors involve overlapping systems, lack of integrated platforms, limited training, and inconsistent digital literacy levels among staff. Digital transformation has improved data accuracy, accountability, motivation, and overall performance. Despite challenges, the transformation has created a more structured and transparent work environment. Sustainable success requires continued system integration, targeted training, and human-centered leadership strategies.